1992
DOI: 10.1111/j.1467-6486.1992.tb00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology, Control and Power: The Centralization and Decentralization Debate Revisited*

Abstract: This article addresses the conceptualization of power in relation to the use of computers in organizations. Commonly held views that the application of computer based information systems leads to either a centralization or a decentralization of power and control, or that computers merely reinforce the power of dominant actors, are criticized, and an alternative view is put forward which focuses on the symbolic and disciplinary dimensions of the development of information systems. This perspective is then illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(107 citation statements)
references
References 23 publications
(12 reference statements)
2
104
0
1
Order By: Relevance
“…Disciplinary technologies are not exclusively constraining. Instead, they open up a new and legitimate discursive space for action (Bloomfield & Coombs, 1992). However, according to the problem we faced, the introduction of the UCAN was bound to bring subtle, negative, yet far-reaching effects on the autonomy of comprehensive/academic universities.…”
Section: Reflectionmentioning
confidence: 99%
“…Disciplinary technologies are not exclusively constraining. Instead, they open up a new and legitimate discursive space for action (Bloomfield & Coombs, 1992). However, according to the problem we faced, the introduction of the UCAN was bound to bring subtle, negative, yet far-reaching effects on the autonomy of comprehensive/academic universities.…”
Section: Reflectionmentioning
confidence: 99%
“…This was inferred as an attempt to compliment the decentralised work processes of teams such as the Notes Team. In fact, any centralisation and decentralisation attempts can be seen as instances of information politics (Bloomfield & Coombs, 1992 From NOESIS system's point of view, the senior managers and long term project staff of the department are still the main contributors to the system. However, with the tactic to use NOESIS as an induction tool for new project managers, the system could play a part in shaping newcomers with the influence of its main contributors.…”
Section: Power Shifts Realised In the Organisationmentioning
confidence: 99%
“…They claim that failure of a system is more or less the embodiment of a perceived situation rather than actual failure of the system, and such embodiments can be the result of a political process. Bloomfield & Coombs (1992) investigated the debate of whether information technology centralises or decentralises power structures in an organisation and concluded that neither is true and that information technologies in place are themselves outcomes of power struggles. Robey & Markus (1984) postulated that system development can be both a rational and a political process; thus it is important for participants to be aware of the rituals that take place in the development process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooper (1994); Tolsby (1998) Impact on distribution of power Bloomfield & Coombs (1992); Poulymenakou and Holmes (1996). Note: a response of 1 indicates always, whilst a response of 5 indicates never Significant at the 1.0 % level;  2 = 12.67 > 11.34  2 (0.010), 3df.…”
Section: Transitional Issues (Ti)mentioning
confidence: 99%